Who shapes education reform policies in Lebanon?. Issue 4 (4th July 2019) - Shuayb, Maha
Abstract: Many Arab countries are currently undergoing significant education reform. However, there is a paucity of research on how reforms are crafted and educational policies constructed. Lebanon has witnessed two education reforms since the Taif Agreement in 1989. This paper examines the role of research centres in influencing the last two education reforms. It selects a case study of an independent, non-governmental educational association and studies the role it played in these two reforms. The study found that contrary to the conventional wisdom, policy makers did call on research institutes when designing their reform. Yet there is a haphazard relationship between policy makers and researcher centres influenced by a number of factors, such as personal relationships, policy brokers, donors, and the availability of reputable research centres. The study also showed reluctance amongst some academics to play a direct role in influencing policymakers decisions.